2021
DOI: 10.3390/ijerph18041936
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Stretching the Hip Flexor Muscles on Performance Parameters. A Systematic Review with Meta-Analysis

Abstract: The hip flexor muscles are major contributors to lumbar spine stability. Tight hip flexors can lead to pain in the lumbar spine, and hence to an impairment in performance. Moreover, sedentary behavior is a common problem and a major contributor to restricted hip extension flexibility. Stretching can be a tool to reduce muscle tightness and to overcome the aforementioned problems. Therefore, the purpose of this systematic review with meta-analysis was to determine the effects of a single hip flexor stretching e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 35 publications
0
11
0
Order By: Relevance
“…With regard to the duration of the application, our meta-analysis showed that intervention durations of >60 s showed a trivial significant greater effect for foam rolling on performance compared with stretching (ES = −0.149; P = 0.002). However, this was not the case for an application duration of ≤ 60 s. According to several reviews, stretching for ≤ 60 s likely has no detrimental effects on performance parameters (Kay and Blazevich, 2012 ; Behm et al, 2016 ; Konrad et al, 2021b ), while stretching for more than 60 s likely has a detrimental effect (Kay and Blazevich, 2012 ; Behm et al, 2016 ) due to a decrease in muscle stiffness (Kay et al, 2015 ; Konrad et al, 2017a , b ) and hence, a negatively affected force production (Monte and Zignoli, 2021 ). For this reason, one could have assumed that, in the included studies of the present analysis with stretching durations of >60 s, the performance would decrease, while this would not be expected following foam rolling.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…With regard to the duration of the application, our meta-analysis showed that intervention durations of >60 s showed a trivial significant greater effect for foam rolling on performance compared with stretching (ES = −0.149; P = 0.002). However, this was not the case for an application duration of ≤ 60 s. According to several reviews, stretching for ≤ 60 s likely has no detrimental effects on performance parameters (Kay and Blazevich, 2012 ; Behm et al, 2016 ; Konrad et al, 2021b ), while stretching for more than 60 s likely has a detrimental effect (Kay and Blazevich, 2012 ; Behm et al, 2016 ) due to a decrease in muscle stiffness (Kay et al, 2015 ; Konrad et al, 2017a , b ) and hence, a negatively affected force production (Monte and Zignoli, 2021 ). For this reason, one could have assumed that, in the included studies of the present analysis with stretching durations of >60 s, the performance would decrease, while this would not be expected following foam rolling.…”
Section: Discussionmentioning
confidence: 99%
“…With regard to other stretching techniques, Behm et al ( 2016 ) reported a mean performance impairment of 3.7% immediately after proprioceptive neuromuscular facilitation (PNF) stretching, but an increase in performance of 1.3% after dynamic stretching. Thus, it can be concluded that the effects of a single stretching exercise on performance are highly dependent on the stretch duration and stretching technique (Behm and Chaouachi, 2011 ; Kay and Blazevich, 2012 ; Behm et al, 2016 ), but are likely also dependent on the muscles stretched [e.g., see the review of the influence of hip flexor muscles in Konrad et al ( 2021b )]. A possible mechanism for a detrimental effect in performance can be found in a decrease in muscle stiffness, especially following longer durations of static stretching (Kay et al, 2015 ; Konrad et al, 2017a , b ).…”
Section: Introductionmentioning
confidence: 99%
“…However, if dynamic stretching is applied, Behm et al (2016) reported mean increases in performance of 1.3%. Thus, performance changes following stretching depend on the stretch duration and stretching technique (Behm et al, 2016;Behm and Chaouachi, 2011;Behm et al, 2021a;Kay and Blazevich, 2012), and are also likely dependent on the muscles stretched (Konrad et al, 2021 . For foam rolling, there seems to be, at least, no detrimental effect on performance (Wiewelhove et al, 2019;Cheatham et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, a meta-analysis study indicated foam rolling (FR) intervention as effective as static stretching to increase ROM (Wilke et al, 2020) without decreasing muscle strength or athletic performance (Sullivan et al, 2013;Lee et al, 2018;Wiewelhove et al, 2019;Phillips et al, 2021). As reported in many previous studies, certain duration static stretching intervention could decrease the muscle strength, the so-called stretch-induced force deficit (Kay and Blazevich, 2012;Behm et al, 2016;Konrad et al, 2021). Thus, FR intervention is considered as an approach that could increase flexibility without decreasing muscle strength.…”
Section: Introductionmentioning
confidence: 99%